Income inequality and redistribution in post-industrial democracies: Demographic, economic, and political determinants - Evelyne Huber; John D. Stephens (Luxembourg Income Study (LIS), 2013)
This article analyzes the determinants of market income distribution and governmental redistribution. The dependent variables are LIS data on market income inequality (measured by the Gini index) for households with a head aged 25 to 59 and the percent reduction in the Gini index by taxes and transfers. We test the generalizability of the Goldin/Katz hypothesis that inequality has increased in the United States because the country failed to invest sufficiently in education. The main determinants of market income inequality are (in order of size of the effect) family structure (single mother households), union density, deindustrialization, unemployment, employment levels, and education spending. The main determinants of redistribution are (in order of magnitude) left government, family structure, welfare state generosity, unemployment, and employment levels. Redistribution rises mainly because needs rise (that is, unemployment and single mother households increase), not because social policy becomes more redistributive.
Keywords: H53; I38; J31; 330; inequality; welfare state; redistribution; Einkommensverteilung; Disparitätsmaß; Gini-Koeffizient; Wirtschaftspolitik; Wirkungsanalyse; USA